The Ageing of Ukraine’s Population: Demographic Trends, Social and Economic Implications - Roman Tesliuk; Vitaliy Krupin (Wieś i Rolnictwo)
The article aims to understand key demographic trends in the past 30 years in Ukraine in terms of ageing. The particular focus is on differences between urban and rural population in order to understand the possible social and economic implications of ageing. The research considers national trends and regional disparities, presenting the key demographic indicators for both. These indicators include the dynamics of population with regard to age groups, demographic dependency, average age, potential support ratio, life expectancy at birth and the changes in the age-sex structure. Analysis reveals a steady ageing trend in the past 30 years, a result of the decrease in fertility and gradual shrinking of the population group aged 0–14 (from 21.6 to 15.5 million) and the simultaneous expansion of the elderly (65+) group (from 11.7 to 16.5 million). The total fertility rate has a downward trend reaching 1.37 (compared to 1.94 in 1989) and the average age has risen to 41.3 years. While similar trends are present for both the urban and rural populations regarding the changes in age groups, and in recent years the differences have been decreasing, in case of the life expectancy at birth these differences are still present, especially for males. Depopulation trends in Ukraine are also intensified by emigration processes. As there are social and economic challenges due to demographic ageing, low life expectancy is a constraint on a further increase in pensionable age.